Flexible polydimethylsiloxane/multi-walled carbon nanotubes membranous metacomposites with negative permittivity - Sun, Kai; Xie, Peitao; Wang, Zhongyang; Su, Tongming; Shao, Qian; Ryu, JongEun; Zhang, Xihua; Guo, Jiang; Shankar, Akash; Li, Jianfeng; Fan, Runhua; Cao, Dapeng; et al. (Polymer (Guilford), 2017)
Metacomposites with negative electromagnetic parameters can be promising substitute for periodic metamaterials. In this paper, we devoted to fabricating flexible metacomposite films, which have great potential applications in the field of wearable cloaks, sensing, perfect absorption and stretchable electronic devices. The conductivity and the complex permittivity were investigated in flexible polydimethylsiloxane (PDMS)/multi-walled carbon nanotubes (MWCNTs) membranous nanocomposites, which were fabricated via in-situ polymerization process. With the increase of conductive one-dimension carbon nanotubes concentration, there was a percolation transition observed in conduction due to the formation of continuous networks. The dielectric dispersion behavior was also analyzed in the spectra of complex permittivity. It is indicated that the conduction and polarization make a combined effect on the dielectric loss in flexible PDMS/MWCNTs composites. The negative permittivity with a dielectric resonance was obtained, and was attributed to the induced electric dipoles. [Display omitted] •Flexible conductive polydimethylsiloxane metacomposites were prepared.•Negative permittivity was observed in the nanocomposites.•Induced electric dipoles attributed to the negative permittivity.